1999
DOI: 10.1111/j.1600-0447.1999.tb07238.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorders in dysthymia and major depression

Abstract: The data indicated that (i) dysthymia--mainly that of early onset--is associated with significantly higher personality disorder comorbidity than episodic major depression, and (ii) the presence of a personality disorder is related to more severe overall psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Research by Cohen and colleagues suggests that depression in adolescence predicts adult PDs [30], and conversely, that PDs in adolescence predict adult Axis I disorders [31]. Among dysthymic adults, Garyfallos et al [32] found early-onset DD to be associated with particularly high PD comorbidity. Whereas single episodes of major depression may not produce lasting personality change [33], recurrent or chronic depression evidently correlates with PDs [6, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Cohen and colleagues suggests that depression in adolescence predicts adult PDs [30], and conversely, that PDs in adolescence predict adult Axis I disorders [31]. Among dysthymic adults, Garyfallos et al [32] found early-onset DD to be associated with particularly high PD comorbidity. Whereas single episodes of major depression may not produce lasting personality change [33], recurrent or chronic depression evidently correlates with PDs [6, 34].…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies in this upcoming research domain found that patients with chronic depression report more socially avoidant behavior than those with episodic depression (Ley et al, 2011). In addition, several studies demonstrated a higher prevalence of comorbid avoidant personality disorder in chronic than in nonchronic depression (Garyfallos et al, 1999;Sanderson et al, 1992). Furthermore, in a study on the effectiveness of the Cognitive Behavioral Analysis System of Psychotherapy (CBASP) for chronic depression, an avoidant coping style was found to be associated with a less favorable treatment outcome (Blalock et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…MDD, anxiety disorders, substance-use disorders, phobias and eating disorders are particularly common dysthymia comorbidities (12, 16Á18). Studies have reported that patients with dysthymia significantly more often exhibit personality psychopathology than do patients with MDD, and this is especially the case among the ones with early onset of their illness (13,15,19). In a population of outpatients with primary dysthymia, Garyfallos and coworkers (13) showed and self-defeating personality disorders (13).…”
mentioning
confidence: 98%
“…Studies have reported that patients with dysthymia significantly more often exhibit personality psychopathology than do patients with MDD, and this is especially the case among the ones with early onset of their illness (13,15,19). In a population of outpatients with primary dysthymia, Garyfallos and coworkers (13) showed and self-defeating personality disorders (13). According to another study, narcissistic and passiveÁaggressive personality disorders were also common among dysthymia patients (15).…”
mentioning
confidence: 98%